Cutaneous Vasculitis and Recurrent Infection Caused by Deficiency in Complement Factor I - Nanthapisal, Sira; Eleftheriou, Despina; Gilmour, Kimberly; Leone, Valentina; Ramnath, Radhika; Omoyinmi, Ebun; Hong, Ying; Klein, Nigel; Brogan, Paul A. (Frontiers in Immunology, 2018)
Cutaneous leukocytoclastic vasculitis arises from immune complex deposition and dysregulated complement activation in small blood vessels. There are many causes, including dysregulated host response to infection, drug reactions, and various autoimmune conditions. It is increasingly recognised that some monogenic autoinflammatory diseases cause vasculitis, although genetic causes of vasculitis are extremely rare. We describe a child of consanguineous parents who presented with chronic cutaneous leukocytoclastic vasculitis, recurrent upper respiratory tract infection, and hypocomplementaemia. A homozygous p.His380Arg mutation in the Complement Factor I gene CFI was identified as the cause, resulting in complete absence of alternative complement pathway activity, decreased classical complement activity, and low levels of serum factor I, C3, and factor H. C4 and C2 levels were normal. The same homozygous mutation and immunological defects were also identified in an asymptomatic sibling. CFI deficiency is thus now added to the growing list of monogenic causes of vasculitis and should always be considered in vasculitis patients found to have persistently low levels of C3 with normal C4.